RANCANG BANGUN ALAT PENGUKUR BERAT DAN DIMENSI PAKET BERBASIS MIKROKONTROLLER MENGGUNAKAN APLIKASI TELEGRAM - Syofian, Andi; Yultrisna, Yultrisna (Ensiklopedia of Journal, 2025)
Currently, people tend to shop for daily necessities online through various marketplaces. Shipping costs depend on three parameters: weight, dimensions, and destination. Generally, these parameters are determined manually using rulers and scales. The solution proposed in this research is to create an automated system for measuring dimensions and weight. The method involves integrating a weight measurement tool using a load cell and a dimension measurement tool using ultrasonic sensors. One load cell is used in a Wheatstone bridge configuration to achieve good sensitivity. Meanwhile, dimension measurement employs five ultrasonic sensors to measure the length, width, and height of the package. The information from all sensors is processed using an ESP32 microcontroller, and the measurement results can be sent to a Telegram application. Testing results showed an average weight measurement error of 1.42% over 15 trials. For dimension measurements, the average errors were 2.17% for length, 1.93% for width, and 2.25% for height over 15 trials.Keywords: Package weight, package dimensions, HC-SR04 ultrasonic sensor, load cell, ESP32, Telegram.